Documents of War: Understanding the Syrian Conflict. Issue 2 (14th April 2015) - Price, Megan; Gohdes, Anita; Ball, Patrick
Abstract: Researchers in Syria are doing their best to monitor the number of people killed in the ongoing conflict. A full and complete count is impossible amid the violence – but the extent to which killings can and cannot be documented reveals much about the nature of the fighting. By Megan Price, Anita Gohdes and Patrick Ball Megan Price, Anita Gohdes and Patrick Ball explain how documentation dynamics help shed light on the Syrian conflict